Special principles for making public policy on firearm circulation in Ukraine - Shumeiko, T. (Garantia Ltd., 2021)
The relevance of the article is the fact that the principles for making public policy on firearm circulation in Ukraine are a set of basic (fundamental) ideas, which contribute in a comprehensive manner to the legitimate, optimal and effective public policy-making in this field in a State that is legal, democratic and social. The aim of the article is to form a relevant scientific understanding of the nature and system of special principles for making public policy on firearm circulation. Results. The importance of the principles for making public policy on firearm circulation derives from the fact that they are a complex, mutually agreed system, since the operation of a system of principles of law implies two levels (orders) of system relations: external or environmental (forward and backward) and internal (i.e., within a system of principles of law). The principles under study are considered as a set of individual sectoral (administrative and legal) and certain basic ideas of public administration, which together contribute to the legitimate, optimal and effective public policy-making in the field of firearm circulation in Ukraine as a legal, democratic and social State. Conclusions. The system of special principles for making public policy on firearm circulation today involves the following principles: 1) openness and transparency; 2) harmonious consistency (non-conflict); 3) objective justification; 4) scientific soundness and harmonization (unity) of theory and practice; 5) reality and completeness; 6) planning and predictability; 7) rationality and efficiency; 8) relative flexibility and timeliness; 9) constancy. Today, in Ukraine, there is no special legislative act on arms trafficking in the country, and therefore, it is necessary to create and adopt a bill on arms trafficking, which will contain an article on a set of principles of arms circulation, which will apply to the formation and implementation of state policy sphere. Актуальність статті полягає в тому, що принципи формування й реалізації державної політики у сфері обігу зброї в Україні є комплексом базових (засадничих) ідей, які сукупно сприяють законному, оптимальному та ефективному формуванню й реалізації державної політики в зазначеній сфері в державі, котра є правовою, демократичною та соціальною. Метою статті є формування актуальної наукової думки щодо сутності та системи спеціальних принципів формування й реалізації державної політики у сфері обігу зброї в Україні. Результати. Важливість принципів формування й реалізації державної політики у сфері обігу зброї зумовлена тим фактом, що вони являють собою складну, взаємоузгоджену систему, оскільки функціонування системи принципів права передбачає виникнення системних зв’язків двох рівнів (порядків): зовнішніх зв’язки, або зв’язків із середовищем (прямих і зворотних), та внутрішньосистемних зв’язків, тобто зв’язків усередині системи принципів права. Досліджені принципи тлумачать як сукупність окремих галузевих (адміністративно-правових) і певних засадничих ідей публічного адміністрування, що сукупно сприяють законному, оптимальному й ефективному формуванню та реалізації державної політики у сфері обігу зброї в Україні як правовій, демократичній і соціальній державі. Висновки. Встановлено, що систему спеціальних принципів формування та реалізації державної політики у сфері обігу зброї в Україні сьогодні становлять такі принципи: 1) відкритості та прозорості; 2) гармонійної узгодженості (неконфліктності); 3) об’єктивної виправданості; 4) наукової обґрунтованості та узгодження (єдності) теорії і практики; 5) реальності та повноти; 6) плановості та очікуваності; 7) раціональності й ефективності; 8) відносної гнучкості та своєчасності; 9) постійності. На сьогодні в Україні відсутній спеціальний законодавчий акт про обіг зброї в державі, а відтак необхідне створення та прийняття законопроєкту про обіг зброї, у якому буде міститися стаття, присвячена комплексу принципів обігу зброї, що поширюватимуться на процеси формування й реалізації державної політики в зазначеній сфері.
Спеціальні принципи формування та реалізації державної політики у сфері обігу зброї в Україні
Keywords: public policy on firearm circulation; firearms; firearm circulation; legal principles; implementation of public policy; special principles; public policy-making; зброя; обіг зброї; державна політика у сфері обігу зброї; правові принципи; реалізація державної політики; спеціальні принципи; формування державної політики